Efficacy of a single-dose regimen of inactivated whole-cell oral cholera vaccine: results from 2 years of follow-up of a randomised trial. Issue 6 (June 2018) - Qadri, Firdausi; Ali, Mohammad; Lynch, Julia; Chowdhury, Fahima; Khan, Ashraful Islam; Wierzba, Thomas F; Excler, Jean-Louis; Saha, Amit; Islam, Md Taufiqul; Begum, Yasmin A; Bhuiyan, Taufiqur R; Khanam, Farhana; et al.
Summary: Background: A single-dose regimen of inactivated whole-cell oral cholera vaccine (OCV) is attractive because it reduces logistical challenges for vaccination and could enable more people to be vaccinated. Previously, we reported the efficacy of a single dose of an OCV vaccine during the 6 months following dosing. Herein, we report the results of 2 years of follow-up. Methods: In this placebo-controlled, double-blind trial done in Dhaka, Bangladesh, individuals aged 1 year or older with no history of receipt of OCV were randomly assigned to receive a single dose of inactivated OCV or oral placebo. The primary endpoint was a confirmed episode of non-bloody diarrhoea for which the onset was at least 7 days after dosing and a faecal culture was positive for Vibrio cholerae O1 or O139. Passive surveillance for diarrhoea was done in 13 hospitals or major clinics located in or near the study area for 2 years after the last administered dose. We assessed the protective efficacy of the OCV against culture-confirmed cholera occurring 7–730 days after dosing with both crude and multivariable per-protocol analyses. This trial is registered at ClinicalTrials.gov, number NCT02027207 . Findings: Between Jan 10, 2014, and Feb 4, 2014, 205 513 people were randomly assigned to receive either vaccine or placebo, of whom 204 700 (102 552 vaccine recipients and 102 148 placebo recipients) were included in the per-protocol analysis. 287 first episodes of cholera (109 among vaccine recipients and 178 among placebo recipients) were detected during the 2-year follow-up; 138 of these episodes (46 in vaccine recipients and 92 in placebo recipients) were associated with severe dehydration. The overall incidence rates of initial cholera episodes were 0·22 (95% CI 0·18 to 0·27) per 100 000 person-days in vaccine recipients versus 0·36 (0·31 to 0·42) per 100 000 person-days in placebo recipients (adjusted protective efficacy 39%, 95% CI 23 to 52). The overall incidence of severe cholera was 0·09 (0·07 to 0·12) per 100 000 person-days versus 0·19 (0·15 to 0·23; adjusted protective efficacy 50%, 29 to 65). Vaccine protective efficacy was 52% (8 to 75) against all cholera episodes and 71% (27 to 88) against severe cholera episodes in participants aged 5 years to younger than 15 years. For participants aged 15 years or older, vaccine protective efficacy was 59% (42 to 71) against all cholera episodes and 59% (35 to 74) against severe cholera. The protection in the older age groups was sustained throughout the 2-year follow-up. In participants younger than 5 years, the vaccine did not show protection against either all cholera episodes (protective efficacy −13%, −68 to 25) or severe cholera episodes (−44%, −220 to 35). Interpretation: A single dose of the inactivated whole-cell OCV offered protection to older children and adults that was sustained for at least 2 years. The absence of protection of young children might reflect a lesser degree of pre-existing natural immunity in this age group. Funding: Bill & Melinda Gates Foundation to the International Vaccine Institute.